2010
DOI: 10.1523/jneurosci.2154-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

 -Amyloid Disrupts Activity-Dependent Gene Transcription Required for Memory through the CREB Coactivator CRTC1

Abstract: Activity-dependent gene expression mediating changes of synaptic efficacy is important for memory storage, but the mechanisms underlying gene transcriptional changes in age-related memory disorders are poorly understood. In this study, we report that gene transcription mediated by the cAMP-response element binding protein (CREB)-regulated transcription coactivator CRTC1 is impaired in neurons and brain from an Alzheimer's disease (AD) transgenic mouse expressing the human ␤-amyloid precursor protein (APP Sw,In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
113
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(123 citation statements)
references
References 70 publications
8
113
0
Order By: Relevance
“…We found a time-dependent differential induction of CREB target Nr4a family genes Nr4a1-3 in the hippocampus, a result that agrees with the requirement of Nr4a genes for contextual memory (44,55). CRTC1-mediated transcription may involve CRTC1 dephosphorylation at Ser151, a critical event for activityinduced CREB-mediated transcription (33,36). Since the histone deacetylase CBP mediates CREBdependent transcription through cooperative interactions with CRTC2 and CREB (26), it is possible that CRTC1 dephosphorylation and nuclear translocation could mediate its recruitment to CREB target promoters through cooperative interactions with CBP and CREB.…”
Section: Discussionsupporting
confidence: 76%
“…We found a time-dependent differential induction of CREB target Nr4a family genes Nr4a1-3 in the hippocampus, a result that agrees with the requirement of Nr4a genes for contextual memory (44,55). CRTC1-mediated transcription may involve CRTC1 dephosphorylation at Ser151, a critical event for activityinduced CREB-mediated transcription (33,36). Since the histone deacetylase CBP mediates CREBdependent transcription through cooperative interactions with CRTC2 and CREB (26), it is possible that CRTC1 dephosphorylation and nuclear translocation could mediate its recruitment to CREB target promoters through cooperative interactions with CBP and CREB.…”
Section: Discussionsupporting
confidence: 76%
“…The expression of some of these IEGs is reduced in AD, as has been shown by in vitro and in vivo experiments (5, 7-9, 11, 12). Most recently, it was reported that gene transcription, mediated by the cAMP-response element binding protein (CREB)-regulated transcription coactivator CRTC1, is impaired in a mouse model of AD (13), further suggesting that Aβ-induced memory deficits may be due to alterations in signaling transduction pathways. CREB is a key immediate early gene involved in learning and memory.…”
mentioning
confidence: 99%
“…While Aβ40 is the predominant cleavage product, the less abundant Aβ42 represents a longer and more amyloidogenic form of Aβ. Moreover, increased cerebrocortical Aβ42 appears to closely correlate with synaptic dysfunction associated with AD (España et al, 2010). The biological study on the action mechanism of compounds 1-4 DOI: 10.4062/biomolther.2011.19.1.090 is in progress.…”
Section: Discussionmentioning
confidence: 99%